2020
DOI: 10.37763/wr.1336-4561/65.4.633644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on the surface color of rubber wood (Hevea brasiliensis)

Abstract: In this study the effect heat treatment process parameters (temperature, duration and heating rate) on the surface color of rubber wood was evaluated. The color of the rubber wood was determined using CIE L*a*b* system before and after the heat treatment. The colorimetric properties, including total color difference (∆E*), lightness index (L*), red-green index (a*), and yellow-blue index (b*), were investigated at different treatment conditions. The results of analysis of variance (ANOVA) indicate that the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The results showed that the natural color of rubberwood (without fungal attack) was yellowish white with an average value of L = 80.11, a = 7.23, b = 20.00, and E = 82.90 (Table 4). Regarding the natural color of the rubberwood, Jiang et al (2020) reported almost the same L, a, and b values, which were 80.94, 4.37, and 21.69, respectively. Meanwhile, after being attacked by the stain fungi, the color changes, depending on the type of isolate of the stain fungi that attacks it.…”
Section: Discoloration Of the Wood Samplesmentioning
confidence: 83%
“…The results showed that the natural color of rubberwood (without fungal attack) was yellowish white with an average value of L = 80.11, a = 7.23, b = 20.00, and E = 82.90 (Table 4). Regarding the natural color of the rubberwood, Jiang et al (2020) reported almost the same L, a, and b values, which were 80.94, 4.37, and 21.69, respectively. Meanwhile, after being attacked by the stain fungi, the color changes, depending on the type of isolate of the stain fungi that attacks it.…”
Section: Discoloration Of the Wood Samplesmentioning
confidence: 83%
“…The change of b * was similar to that of L * that decreasing from 27.47 (control) to 20.56 (200 C) (Figure 3). Most studies have reported that the increasing HT temperature decreased the b * of rubber wood, 33 beech wood, 22 and eucalypt wood. 12 For oak wood, the b * dropped from 20.17 (control) to 18.84 (160 C) and further significantly to 3.26 (240 C) with increasing HT temperature.…”
Section: Colour Distribution Change Of Wood Due To Heat Treatmentmentioning
confidence: 99%
“…23 For plane wood, a * was affected very little by HT temperature (160 C to 200 C). 16 For the rubber wood (from 170 C to 210 C), 33 eucalypt wood (from 170 C to 200 C), 12 beech wood (from 210 C to 250 C), 22 and Cypress wood (from 160 C to 200 C), 16 the a * first F I G U R E 1 Density variation of samples F I G U R E 2 Layout of measurement points on the wood surface increased for less intensive treatments and then decreased afterwards. For pine wood, the a * presented a large variation that its tendency to increase and decrease alternated throughout the HT process.…”
Section: Colour Distribution Change Of Wood Due To Heat Treatmentmentioning
confidence: 99%
“…Through consumer preference testing, it is known that heat-treated wood with a darker color is more popular with consumers than wood without heat treatment with a lighter color. In order to achieve a deeper "teak color," Jiang et al (2020) used the CIE L*a*b* system to determine the effect of heat treatment process parameters (temperature, duration, and heating rate) on the color of rubber wood (Hevea brasiliensis) before and after heat treatment in order to obtain the best process parameters. The results showed that the temperature significantly affected the colorimetric parameters of the heat-treated rubber wood, while the duration and heating rate had no significant effect.…”
Section: Appearance (Color) Changementioning
confidence: 99%